Titanium-series polyester catalyst with high matting agent tolerance as well as preparation method and application of titanium-series polyester catalyst

Through the chelating structure of conjugated aromatic β-dione and α-hydroxy acid with titanium active center, the problem of poor tolerance of titanium catalysts to matting agents is solved, and high tolerance and stability of matting agents are achieved. Industrial polyester production.

CN119176830APending Publication Date: 2024-12-24ZHEJIANG HENGYI PETROCHEMICAL RES INST CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411131882.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The poor tolerance of titanium catalysts to matting agents leads to irreversible inactivation during polymerization, affecting the melt viscosity of the polyester and the stability of the production system, making it difficult to replace traditional antimony catalysts.

Method used

The conjugated aromatic β-dione and aromatic or alicyclic α-hydroxy acids as compound ligands form a stable chelating structure with the titanium active center to prepare a high matting agent to resist titanium polyester catalyst. Can be added at any stage, keeping activity unaffected.

Benefits of technology

It improves the tolerance, stability and thermal stability of titanium catalysts to matting agents, solves the problems of viscosity growth and system instability during polymerization, and is suitable for industrial-scale polyester production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004998169340000031
    Figure BDA0004998169340000031
  • Figure BDA0004998169340000041
    Figure BDA0004998169340000041
  • Figure BDA0004998169340000121
    Figure BDA0004998169340000121
Patent Text Reader

Abstract

The invention relates to the field of polyester synthesis, and discloses a high-matting-agent-tolerance titanium polyester catalyst as well as a preparation method and application thereof. Conjugated aromatic beta-diketone and alpha-hydroxy acid containing an aromatic ring or an alicyclic ring are adopted as compound ligands to form a stable chelating structure with a titanium active center in a bidentate coordination manner, and the liquid titanium polyester catalyst with high matting agent tolerance, which has good hydrolysis resistance, water solubility, alcohol solubility and thermal stability, is prepared. The activity of the catalyst is not inhibited by a delustering agent, the tolerance to the delustering agent is good, the catalyst can be added at any stage before slurry preparation, esterification, polycondensation and the like, and the activity is not influenced; semi-dull or full-dull titanium polyester in-situ polymerization is carried out, the vacuum allowance of polycondensation is high, and the polymerization process is stable and controllable; the synthesized extinction polyester is good in hue and thermal stability, small in viscosity reduction in the melt spinning process and uniform in fiber mechanical property, and has good industrial application prospects and value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyester synthesis, and in particular to a titanium-based polyester catalyst with high matting agent tolerance, and a preparation method and application thereof. Background Art

[0002] Polyethylene terephthalate (PET) is the world's largest and most widely used thermoplastic polyester material with good mechanical and thermal properties. It is widely used in packaging, clothing, home textiles, electrical appliances, construction, automotive, medical and health fields. In recent years, with the rapid development of the economy, China's polyester industry has gradually improved its global market position. By the end of 2023, the total domestic polyester production capacity has exceeded 75 million tons / year, and China has become the global polyester production and consumption center.

[0003] At present, the most commonly used polycondensation catalyst in the polyester industry is still the antimony catalyst. Although the catalytic activity is moderate and the hue and properties of the synthetic polyester are good, antimony is a heavy metal element and is easily precipitated during the dyeing and finishing of textiles and alkali reduction, causing water pollution. Even in the landfill and incineration recovery of waste polyester, there is also the problem of antimony pollution. Titanium is known as "healthy titanium" and is widely used in various artificial joints, dental implants, etc. It is non-toxic to the human body. In addition, titanium-catalyzed polyester polycondensation reaction is extremely active and the addition amount is small, which can greatly reduce the production cost of polyester. Therefore, in recent years, many scientific research institutes and enterprises at home and abroad have been committed to the research of new titanium catalysts, overcoming the problem of poor hydrolysis stability of titanium catalysts, and through the passivation of titanium catalytic activity, to a certain extent, alleviated the defects of titanium polyester such as thermal degradation, many side reactions, and easy yellowing.

[0004] The above research results have certain reference significance for production, but most of them are currently in the stage of laboratory pilot research. With the promotion to large-scale polyester continuous industrial production lines, titanium-based catalysts have gradually exposed technical difficulties such as poor tolerance to matting agents, poisoning and deactivation, and difficulty in polycondensation and viscosity increase, resulting in unqualified polyester melt viscosity, unstable operation of polymerization production systems, and difficulty in increasing device load, making it difficult for titanium-based catalysts to replace traditional antimony catalysts. Matting agent is an indispensable auxiliary agent for fiber-grade polyester synthesis. Its essential composition is inorganic TiO2, commonly known as titanium dioxide. The semi-matt or fully matt polyester produced by adding titanium dioxide has a good matt effect and an elegant and soft luster. Its fabric also has better light-shielding, drape and deep dyeing properties. Although titanium-based catalysts have extremely high intrinsic catalytic activity when synthesizing high-gloss polyester, they are irreversibly inactivated after contact with matting agents. There are two reasons for the inhibition of its activity: First, in the diol medium, the surface of TiO2 is negatively charged, and it is adsorbed by electrostatic adsorption to the titanium active center (Ti +4) combination, which limits the activity and mass transfer effect of the titanium catalyst; secondly, the TiO2 surface is rich in hydroxyl groups (Ti-OH), and an ester exchange reaction occurs between the titanium catalyst and Ti-OH. The titanium active center is anchored on the submicron TiO2 surface by chemical bonding, resulting in inhibition of activity. Studies have shown that the longer the contact time between the two, the more serious the poisoning of the titanium catalyst. In order to reduce the degree of inhibition, at present, in the synthesis process of titanium polyester, at least one of the titanium catalyst or matting agent must be added after esterification. The online addition technology is difficult and the mixing effect is weakened.

[0005] Patent CN102219894A discloses a titanium catalyst containing sulfonic acid or sulfonate additives, and believes that sulfonic acid or sulfonate additives can reduce the inhibitory effect of matting agents on the activity of titanium catalysts. However, sulfonic acid or sulfonate compounds react violently with metal catalysts, generating impurities during the polymerization process, causing the polyester melt to increase in pressure, which is not conducive to spinning; the patent clearly requires that the matting agent can only be added after esterification and before polycondensation during the polymerization process. Adding matting agents online in the pipeline has the risk of blockage and is not conducive to the dispersion of the matting agent. Patent CN106336502A discloses a method for producing semi-matte or fully matte titanium polyesters in which matting agents can be added before and after esterification, but the titanium catalyst used also adds sulfonate additives, which affects the quality and spinnability of the polyester. Patent WO2003 / 016378 discloses a method for producing matte titanium polyester by using coated titanium dioxide, which requires inorganic coating and organic modification of the titanium dioxide surface. The production cost of the matte agent is high, and it has no practical significance for the promotion of titanium polyester catalysts.

[0006] In summary, there is an urgent need to continuously develop new titanium-based polyester catalysts that have high matting agent tolerance and do not affect the quality and spinnability of polyester. Summary of the invention

[0007] In order to overcome the problems existing in the prior art, especially the poor tolerance of titanium catalysts to matting agents, irreversible deactivation during polymerization leading to difficulty in polycondensation of matting titanium polyester, the present invention provides a high matting agent tolerance titanium polyester catalyst and its preparation method and application. The present invention adopts conjugated aromatic β-diketones and α-hydroxy acids containing aromatic rings or alicyclic rings as composite ligands to form a stable chelate structure with the titanium active center in a bidentate coordination manner, and prepares a liquid high matting agent tolerance titanium polyester catalyst with good hydrolysis resistance, water solubility, alcohol solubility and thermal stability. The activity of the catalyst is not inhibited by the matting agent, and has good tolerance to the matting agent. It can be added at any stage such as slurry preparation, esterification, and before polycondensation, and the activity is not affected; semi-matting or fully matting titanium polyester is polymerized in situ, the polycondensation vacuum margin is high, and the polymerization process is stable and controllable; the synthesized matting polyester has good hue and thermal stability, the viscosity drop is small during melt spinning, and the fiber mechanical properties are uniform, which has good industrial application prospects and value.

[0008] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a titanium-based polyester catalyst with high matting agent tolerance, comprising an alkoxytitanium diol ester as a catalytically active ingredient, and a conjugated aromatic β-diketone and an aromatic or alicyclic α-hydroxy acid chelated with the alkoxytitanium diol ester in sequence.

[0009] Among them: the conjugated aromatic β-diketone forms a six-membered ring chelate structure with the titanium active center of the alkoxy titanium diol ester through bidentate coordination; the α-hydroxy acid containing an aromatic ring or an alicyclic ring forms a five-membered ring chelate structure with the titanium active center of the alkoxy titanium diol ester through hydroxyl and carboxylic acid.

[0010] The present invention introduces a conjugated aromatic β-diketone and an α-hydroxy acid containing an aromatic ring or an alicyclic ring as a complex ligand: the aromatic β-diketone has a π-π conjugated structure and is an electron-rich ligand, which is combined with the titanium active center in the form of multi-dentate coordination to regulate the positive charge of titanium; the α-hydroxy acid containing an aromatic ring or an alicyclic ring can adjust the polarity of the catalyst, improve the compatibility of the titanium catalyst in the aqueous phase or alcohol system, and form a stable five-membered ring chelate structure with the titanium active center through the hydroxyl and carboxylic acid structures. Compared with conventional monoalkoxy titanate catalysts, the binding force between the chelated macromolecular titanium catalyst of the present invention and the surface of titanium dioxide is weakened: firstly, the chelation effect can effectively regulate the electronic structure of the titanium active center and weaken the electrostatic adsorption tendency between the titanium active center and the titanium dioxide interface; secondly, the complex ligand of the aromatic ring substituent or the alicyclic substituent provides a large steric hindrance, which hinders the contact between the titanium catalyst and the matting agent and interferes with the anchoring problems such as adsorption and reaction of the titanium catalyst on the titanium dioxide surface, thereby improving the tolerance of the titanium catalyst to the matting agent and preventing its activity from being interfered with by the matting agent.

[0011] In summary, the titanium-based polyester catalyst of the present invention has good hydrolysis resistance, water solubility, alcohol solubility, thermal stability and matting agent tolerance, and is suitable for the synthesis of various polyester materials. In particular, it overcomes the problem of irreversible deactivation of the titanium-based catalyst after contacting the titanium dioxide matting agent, which leads to difficulty in viscosity growth. When the semi-matt or fully matt titanium-based polyester is polymerized in situ, the titanium catalyst and matting agent prepared by the present invention can be added at any stage such as slurry preparation, esterification, and before polycondensation, and the activity is not affected, the polycondensation vacuum margin is high, and the polymerization process is stable and controllable. The matt polyester synthesized using the catalyst has good hue and thermal stability.

[0012] Preferably, the alkoxytitanium is selected from at least one of tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetraisopropyl titanate, tetrabutyl titanate and tetraisooctyl titanate.

[0013] Preferably, the conjugated aromatic β-diketone is selected from benzoyl acetone (KL 1), benzoyl trifluoroacetone (KL 2 ), 2-naphthoyltrifluoroacetone (KL 3 ), dibenzoylmethane (KL 4 ), 4,4′-dibromodibenzoylmethane (KL 5 ), dinaphthoyl methane (KL 6 ) and bipyridine-2-formylmethane (KL 7 ), more preferably benzoyl acetone (KL 1 ), dibenzoylmethane (KL 4 ), most preferably dibenzoylmethane (KL 4 ).

[0014] Preferably, the molar ratio of the conjugated aromatic β-diketone to the alkoxytitanium is 0.2 to 4:1, more preferably 1 to 1.5:1.

[0015] Preferably, the α-hydroxy acid containing an aromatic ring or an alicyclic ring is selected from mandelic acid (AL 1 ), benzyl alcohol acid (AL 2 ), lactobionic acid (AL 3 ) and N-acetylneuraminic acid (AL 4 ), more preferably lactobionic acid (AL 3 ).

[0016] After the first ligand conjugated aromatic β-diketone is coordinated with titanium, the polarity of the catalyst molecule becomes weaker and the water solubility becomes worse. Introducing an α-hydroxy acid containing an aromatic ring or an alicyclic ring and containing a polar group as the second ligand can effectively improve the water solubility and alcohol solubility of the catalyst.

[0017] The present invention team also found through research that the larger the molecular structure of the ligand, the more conducive it is to weaken the adsorption and reaction between the titanium active center and the matting agent through the steric hindrance effect, thereby improving the tolerance of the titanium catalyst to the matting agent. Therefore, the second ligand is preferably an α-hydroxy acid containing an aromatic ring or an alicyclic ring. However, the steric hindrance of the conjugated aromatic β-diketone containing aromatic substitution becomes larger after the chelation reaction with titanium, which may make the chelation reaction of the second ligand difficult. Therefore, the coordinating carboxyl and hydroxyl groups of the second ligand need to have stronger coordination ability. Therefore, the structural coordination effect of the α-carbon atom away from the cyclic substituent is better. After a large number of screening experiments, the second ligand is most preferably AL 3 Lactobionic acid.

[0018] Preferably, the molar ratio of the aromatic or alicyclic α-hydroxy acid to the alkoxytitanium is 0.2 to 4:1, more preferably 0.5 to 1.5:1.

[0019] Preferably, the catalyst further comprises at least one selected from the group consisting of sodium acetate, potassium acetate, magnesium acetate, calcium acetate, zinc acetate, lanthanum acetate and cerium acetate.

[0020] Preferably, the molar ratio of the co-catalyst to the alkoxytitanium is 0.2 to 2:1, more preferably 0.5 to 1:1.

[0021] Preferably, the present invention further comprises a stabilizer, selected from at least one of orthophosphoric acid, phosphorous acid, hypophosphorous acid, phosphonic acid or their derivatives; further preferably selected from phosphoric acid, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tripropyl phosphite, hypophosphorous acid, phenylphosphonic acid, methylphosphonic acid, triethyl phosphonoacetate, pyrophosphoric acid, tetraethyl pyrophosphate, preferably at least one of triethyl phosphate, triethyl phosphite, triphenyl phosphite and triethyl phosphonoacetate.

[0022] Preferably, the mass ratio of phosphorus atoms in the stabilizer to titanium atoms in the titanium alkoxide is 0.02 to 1:1, more preferably 0.2 to 0.6:1.

[0023] Preferably, the diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, butylene glycol and pentanediol.

[0024] In a second aspect, the present invention provides a method for preparing the above-mentioned titanium-based polyester catalyst with high matting agent tolerance, comprising: 1) dispersing alkoxy titanium in a diol for ester exchange reaction to obtain an ester exchange solution; adding an alcohol solution of conjugated aromatic β-diketone to the ester exchange solution for chelation to obtain an orange-yellow clear intermediate solution.

[0025] 2) adding an α-hydroxy acid containing an aromatic ring or an alicyclic ring to the orange-yellow intermediate solution obtained in step 1) for chelation; adding a base to adjust the acidity of the system and continuing the chelation; distilling to remove low-boiling point small molecules to obtain a titanium-based polyester catalyst with high matting agent tolerance.

[0026] The present invention can smoothly coordinate and combine the two ligands with the alkoxytitanium diol ester by the above method, thereby obtaining a titanium-based polyester catalyst with high matting agent tolerance. It should be emphasized that the coordination order of the above two ligands is more critical. Conjugated aromatic β-diketone contains aromatic ring substituents with a two-dimensional planar structure; alicyclic α-hydroxy acids have a multi-hydroxy substitution structure. After research, the present invention found that if the coordination reaction order of the two is swapped, the coordination effect and catalytic performance will deteriorate. The reason is that the steric hindrance effect of the two ligands is different. The alicyclic substituent in the α-hydroxy acid contains multiple hydroxy substituents, and the steric hindrance is much greater than that of the β-diketone containing a two-dimensional planar substituent. After swapping the reaction order, it becomes difficult for β-diketone to react with titanium, and the coordination effect deteriorates.

[0027] Preferably, in 1), the conditions of the transesterification reaction are: temperature 60-120° C., time 1-3 h.

[0028] Preferably, in 1), the chelating conditions are: chelating reaction at 60-120° C. for 2-6 hours.

[0029] Preferably, in 1), the mass ratio of the diol to the alkoxytitanium is 0.5 to 10:1, more preferably 3 to 5:1.

[0030] Preferably, in 1), the alcohol solvent of the alcohol solution of the conjugated aromatic β-diketone is selected from at least one of methanol, ethanol, isopropanol, chloroethanol and 1-chloro-2-propanol, and more preferably ethanol and chloroethanol.

[0031] Preferably, in 1), the mass ratio of the alcohol solvent to the conjugated aromatic β-diketone is 1 to 20:1, more preferably 2 to 5:1.

[0032] Preferably, in 1), the feeding rate of the conjugated aromatic β-diketone alcohol solution is 10 to 30 mL / min, more preferably 10 to 20 mL / min.

[0033] Preferably, in 2), the chelating conditions are: temperature 80-150° C., time 1-2 h.

[0034] Preferably, in 2), the pH of the system after adding alkali to adjust the acidity is 3-4.

[0035] For ligands coordinated by carboxyl groups, pH value has a certain influence on their coordination ability: (1) In a strongly acidic environment, due to the high concentration of hydrogen ions, they are distributed around the carboxyl oxygen through electrostatic adsorption, interfering with the coordination of the carboxyl group; (2) Under alkaline conditions, the carboxyl group exists in the form of anions, the exposure of the carboxyl oxygen increases, and thus the coordination ability is enhanced. In order to improve the reaction effect of the second coordination, the inventors found through a large number of experiments that initially increasing the pH value is indeed beneficial to the coordination of α-hydroxy acids, but when the pH value is adjusted too high, it is found that the catalyst intermediate will hydrolyze. Therefore, after process optimization, the pH value is preferably 3-4.

[0036] Preferably, in 2), the chelation continues for 2 to 4 hours.

[0037] Preferably, in 2), the α-hydroxy acid containing an aromatic ring or an alicyclic ring is added in the form of a solution, and the solvent is selected from at least one of water, methanol, ethanol, isopropanol and diethyl ether, and water and ethanol are further preferred; the mass ratio of the solvent to the α-hydroxy acid containing an aromatic ring or an alicyclic ring is 0.5 to 10:1.

[0038] Preferably, in 1), the titanium alkoxide is dispersed in the diol together with the co-catalyst.

[0039] Preferably, in 2), a stabilizer is added after continuing the chelation and before distillation.

[0040] In a third aspect, the present invention provides the use of the above-mentioned titanium-based polyester catalyst with high matting agent tolerance in the synthesis of matting polyester.

[0041] Preferably, the method for synthesizing the extinction polyester comprises: using dicarboxylic acid and / or its ester derivatives and diol as raw materials, performing an esterification reaction to obtain an esterification product, and then performing pre-polycondensation and final polycondensation to obtain the extinction polyester.

[0042] In the above process, titanium dioxide matting agent and high matting agent tolerance titanium polyester catalyst are added at any stage before esterification, during the esterification process or after the esterification, which solves the limitation that the current polyester continuous production line must add online in the esterification to polycondensation pipeline, making production more flexible and reducing the risk of blockage in online addition. At the same time, when the titanium polyester is converted to production, the original feeding port of the polyester device can be used, reducing the cost of technical transformation.

[0043] Preferably, the titanium dioxide matting agent is added in an amount of 0.2 to 2.2 wt % of the matting polyester.

[0044] Preferably, the addition amount of the high matting agent resistant titanium-based polyester catalyst is 4 to 20 ppm of the matting polyester, calculated as titanium atoms.

[0045] Preferably, the dicarboxylic acid and / or its ester-forming derivative is at least one of terephthalic acid, phthalic acid, isophthalic acid, biphenyl dicarboxylic acid, 5-sodium sulfoisophthalate, dimethyl terephthalate, diethyl terephthalate, furandicarboxylic acid, oxalic acid, succinic acid and adipic acid.

[0046] Preferably, the diol is at least one of ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, butylene glycol and pentanediol.

[0047] Preferably, the conditions of the esterification reaction are: temperature 220-260° C., pressure 0-0.4 MPa.

[0048] Preferably, the conditions for the preliminary polycondensation are: 250-290° C., 10-15 kPa; and the conditions for the final polycondensation are: 250-290° C., 50-150 Pa.

[0049] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention uses conjugated aromatic β-diketones and alicyclic α-hydroxy acids as complex ligands to chelate with titanium to prepare a homogeneous titanium-based polyester catalyst with good hydrolysis resistance, alcohol miscibility, and thermal stability. The catalytic system is easy to disperse, stable in long-term storage, does not contain heavy metal antimony, is non-toxic and environmentally friendly, and is suitable for industrial applications.

[0050] (2) In the titanium-based polyester catalyst prepared by the present invention, the conjugated aromatic β-diketone electron-rich ligand and the alicyclic α-hydroxy acid polar ligand have a synergistic effect. The two form a stable chelate structure with the titanium active center in a bidentate coordination manner, which has the following advantages: ① It can effectively regulate the electronic structure of the titanium active center and weaken the electrostatic adsorption tendency between titanium and the matting agent; ② The aromatic ring / alicyclic substituent of the ligand provides steric hindrance to block the contact between the titanium active center and the matting agent, thereby inhibiting the strong adsorption of the titanium catalyst on the titanium dioxide surface and anchoring problems such as exchange reaction, so that the catalyst maintains good diffusion and mass transfer effects, and thus has good matting agent tolerance; ③ The chelate structure and the stabilizer work synergistically, which is beneficial to improving the selectivity of the titanium catalyst and reducing the thermal oxidation degradation side reactions. The synthesized titanium-based polyester product has high thermal stability and good hue.

[0051] (3) The titanium-based polyester catalyst prepared by the present invention has high tolerance to matting agents, few polymerization side reactions, good polyester hue, and stable catalytic activity. It can effectively improve the stability of the polymerization process and release the production capacity of the polyester device, thereby increasing the start-up load and reducing production costs. In addition, the titanium catalyst can be added at any position before polycondensation, thereby avoiding the risk of clogging caused by online addition of the pipeline, while saving the technical transformation cost of the traditional polyester device, which is conducive to the application and promotion of the titanium catalyst.

[0052] (4) The present invention does not involve the use of sulfonic acid or sulfonate additives, which is beneficial to reducing the generation of melt impurities, thereby improving the quality of polyester products and their spinning processing performance. DETAILED DESCRIPTION

[0053] The present invention will be further described below in conjunction with the embodiments.

[0054] Overall embodiment In a first aspect, a titanium-based polyester catalyst with high matting agent tolerance includes an alkoxytitanium diol ester as a catalytically active component, and a conjugated aromatic β-diketone and an aromatic or alicyclic α-hydroxy acid chelated with the alkoxytitanium diol ester in sequence.

[0055] Among them: the conjugated aromatic β-diketone forms a six-membered ring chelate structure with the titanium active center of the alkoxy titanium diol ester through bidentate coordination; the α-hydroxy acid containing an aromatic ring or an alicyclic ring forms a five-membered ring chelate structure with the titanium active center of the alkoxy titanium diol ester through hydroxyl and carboxylic acid.

[0056] In some specific implementation cases, the alkoxytitanium is selected from at least one of tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetraisopropyl titanate, tetrabutyl titanate and tetraisooctyl titanate.

[0057] In some specific implementation cases, the conjugated aromatic β-diketone is selected from benzoyl acetone (KL 1 ), benzoyl trifluoroacetone (KL 2 ), 2-naphthoyltrifluoroacetone (KL 3 ), dibenzoylmethane (KL 4 )、4,4′-dibromodibenzoylmethane (KL 5 ), dinaphthoyl methane (KL 6 ) and bipyridine-2-formylmethane (KL 7 ), more preferably benzoyl acetone (KL 1 ), dibenzoylmethane (KL 4 ), most preferably dibenzoylmethane (KL 4 ). In some specific implementation cases, the molar ratio of the conjugated aromatic β-diketone to the alkoxytitanium is 0.2 to 4:1, and more preferably 1 to 1.5:1.

[0058] In some specific implementation cases, the α-hydroxy acid containing an aromatic ring or an alicyclic ring is selected from mandelic acid (AL 1 ), benzyl alcohol acid (AL 2 ), lactobionic acid (AL 3 ) and N-acetylneuraminic acid (AL 4 ), more preferably lactobionic acid (AL 3 ).

[0059] In some specific implementation cases, the molar ratio of the aromatic or alicyclic α-hydroxy acid to alkoxytitanium is 0.2 to 4:1, and more preferably 0.5 to 1.5:1.

[0060] In some specific implementation cases, a promoter is also included, which is at least one selected from sodium acetate, potassium acetate, magnesium acetate, calcium acetate, zinc acetate, lanthanum acetate and cerium acetate. The molar ratio of the promoter to the alkoxytitanium is 0.2 to 2:1, and more preferably 0.5 to 1:1.

[0061] In some specific implementation cases, a stabilizer is also included, selected from at least one of orthophosphoric acid, phosphorous acid, hypophosphorous acid, phosphonic acid or their derivatives; further preferably selected from phosphoric acid, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tripropyl phosphite, hypophosphorous acid, phenylphosphonic acid, methylphosphonic acid, triethyl phosphonoacetate, pyrophosphoric acid, tetraethyl pyrophosphate, preferably at least one of triethyl phosphate, triethyl phosphite, triphenyl phosphite and triethyl phosphonoacetate. The mass ratio of phosphorus atoms in the stabilizer to titanium atoms in the alkoxy titanium is 0.02 to 1:1, and further preferably 0.2 to 0.6:1.

[0062] In some specific implementation cases, the diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, butylene glycol, and pentanediol.

[0063] In a second aspect, a method for preparing the above-mentioned titanium-based polyester catalyst with high matting agent tolerance comprises: 1) Dispersing alkoxytitanium in diol for ester exchange reaction to obtain an ester exchange solution; adding an alcohol solution of conjugated aromatic β-diketone to the ester exchange solution for chelation to obtain an orange-yellow clear intermediate solution.

[0064] In some specific implementation cases, the conditions of the transesterification reaction are: temperature 60-120°C, time 1-3 hours. The conditions of the chelation are: chelation reaction at 60-120°C for 2-6 hours. The mass ratio of the diol to the alkoxy titanium is 0.5-10:1, and more preferably 3-5:1.

[0065] In some specific implementation cases, the alcohol solvent of the alcohol solution of the conjugated aromatic β-diketone is selected from at least one of methanol, ethanol, isopropanol, chloroethanol and 1-chloro-2-propanol, and ethanol and chloroethanol are more preferred. The mass ratio of the alcohol solvent to the conjugated aromatic β-diketone is 1 to 20:1, and more preferably 2 to 5:1.

[0066] In some specific implementation cases, the feeding rate of the conjugated aromatic β-diketone alcohol solution is 10 to 30 mL / min, and more preferably 10 to 20 mL / min.

[0067] In some specific implementation cases, the titanium alkoxide is dispersed in the diol together with the co-catalyst.

[0068] 2) adding an α-hydroxy acid containing an aromatic ring or an alicyclic ring to the orange-yellow intermediate solution obtained in step 1) for chelation; adding a base to adjust the acidity of the system and continuing the chelation; distilling to remove low-boiling point small molecules to obtain a titanium-based polyester catalyst with high matting agent tolerance.

[0069] In some specific implementation cases, the chelation conditions are: temperature 80-150° C., time 1-2 hours, pH of the system after adding alkali to adjust the acidity is 3-4, and the chelation continues for 2-4 hours.

[0070] In some specific implementation cases, the α-hydroxy acid containing an aromatic ring or an alicyclic ring is added in the form of a solution, and the solvent is selected from at least one of water, methanol, ethanol, isopropanol and ether, and water and ethanol are further preferred; the mass ratio of the solvent to the α-hydroxy acid containing an aromatic ring or an alicyclic ring is 0.5 to 10:1.

[0071] In some specific implementation cases, a stabilizer is added after the chelation and before the distillation.

[0072] In a third aspect, a method for synthesizing a matte polyester comprises: using a dicarboxylic acid and / or its ester derivatives and a diol as raw materials, performing an esterification reaction to obtain an esterification product, and then performing pre-polycondensation and final polycondensation to obtain a matte polyester.

[0073] In the above process, titanium dioxide matting agent and high matting agent tolerance titanium polyester catalyst are added before esterification, during the esterification process or at any stage before polycondensation, which solves the limitation that the current polyester continuous production line must add online in the esterification to polycondensation pipeline, making production more flexible and reducing the risk of blockage during online addition. At the same time, when the titanium polyester is converted to production, the original feed port of the polyester device can be used, reducing the cost of technical transformation.

[0074] In some specific implementation cases, the titanium dioxide matting agent is added in an amount of 0.2-2.2 wt % of the matting polyester, and the high matting agent tolerant titanium polyester catalyst is added in an amount of 4-20 ppm of the matting polyester, calculated as titanium atoms.

[0075] In some specific implementation cases, the dicarboxylic acid and / or its ester-forming derivative is at least one of terephthalic acid, phthalic acid, isophthalic acid, biphenyl dicarboxylic acid, 5-sodium sulfoisophthalate, dimethyl terephthalate, diethyl terephthalate, furandicarboxylic acid, oxalic acid, succinic acid and adipic acid. The diol is at least one of ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, butanediol and pentanediol.

[0076] In some specific implementation cases, the conditions of the esterification reaction are: temperature 220-260° C., pressure 0-0.4 MPa. The conditions of the pre-polycondensation are: 250-290° C., 10-15 kPa; the conditions of the final polycondensation are: 250-290° C., 50-150 Pa.

[0077] Specific Examples and Comparative Examples Example 1 102.1 g (1.64 mol) of ethylene glycol, 34.03 g (0.1 mol) of tetrabutyl titanate and 4.1 g (0.05 mol) of sodium acetate were added to a three-necked flask equipped with a magnetic stirrer, a thermometer and a condenser, stirred and heated to dissolve, and the ester exchange reaction was carried out at 70 ° C for 1 h; 16.52 g (0.1 mol) of KL 1 Benzoyl acetone was dissolved in 49.56 g of ethanol to prepare a solution, which was added to the ester exchange solution at a rate of 10 mL / min and refluxed for 3 h to obtain an intermediate. 2Benzoic acid was dissolved in 45.64g of ethanol, then added to the intermediate solution, heated to 80°C for chelation reaction for 1h, 25wt% sodium hydroxide solution was added to adjust the pH to 3, and the chelation reaction was continued for 2h; 8.68g (0.062mol) of trimethyl phosphate was added, and small molecules were removed by reduced pressure distillation during the reaction to obtain a liquid titanium catalyst. The catalyst preparation conditions are shown in Table 1.

[0078] 830g of terephthalic acid, 387g of ethylene glycol, the titanium catalyst prepared above, and the matting agent slurry are added to the polymerization kettle for slurrying, wherein the amount of titanium catalyst added is 6ppm, based on the weight of Ti atoms relative to the polyester, and the amount of matting agent added is 0.3%, based on the weight of titanium dioxide relative to the polyester. After nitrogen replacement, the esterification reaction is carried out at 220-260°C and 0-0.4MPa, and the esterification water is discharged through separation in the process tower and cooling in the condenser. After the esterification is completed, the vacuum is evacuated and the decompression is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0079] Example 2 Add 102.1g (1.64mol) of ethylene glycol, 34.03g (0.1mol) of tetrabutyl titanate and 4.1g (0.05mol) of sodium acetate into a three-necked flask equipped with a magnetic stirrer, a thermometer and a condenser, stir and heat to dissolve, and perform transesterification at 70°C for 1h; add 33.64g (0.15mol) of KL 4 Dibenzoylmethane was dissolved in 100.91 g of chloroethanol to prepare a solution, which was added to the ester exchange solution at a rate of 20 mL / min and refluxed for 3 h to obtain an intermediate. 2 Benzoic acid was dissolved in 22.82g of ethanol, then added to the intermediate solution, heated to 80°C for chelation reaction for 1h, 25wt% sodium hydroxide solution was added to adjust the pH to 3, and the chelation reaction was continued for 2h; 11.3g (0.062mol) of triethyl phosphate was added, and small molecules were removed by reduced pressure distillation during the reaction to obtain a liquid titanium catalyst. The catalyst preparation conditions are shown in Table 1.

[0080] 830g of terephthalic acid, 387g of ethylene glycol, the titanium catalyst prepared above, and the matting agent slurry are added to the polymerization kettle for slurrying, wherein the titanium catalyst is added in an amount of 6ppm, based on the weight of Ti atoms relative to the polyester, and the matting agent is added in an amount of 0.3%, based on the weight of titanium dioxide relative to the polyester. After nitrogen replacement, the esterification reaction is carried out at 220-260°C and 0-0.4MPa, and the esterification water is discharged through separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the vacuum is evacuated and the decompression is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0081] Example 3 102.1 g (1.64 mol) of ethylene glycol, 34.03 g (0.1 mol) of tetrabutyl titanate and 4.1 g (0.05 mol) of sodium acetate were added to a three-necked flask equipped with a magnetic stirrer, a thermometer and a condenser, stirred and heated to dissolve, and the ester exchange reaction was carried out at 80 ° C for 2 h; 33.64 g (0.15 mol) of KL 4 Dibenzoylmethane was dissolved in 100.91 g of chloroethanol to prepare a solution, which was added to the ester exchange solution at a rate of 20 mL / min and refluxed for 3 h to obtain an intermediate. 3 Lactobionic acid was dissolved in 161.2 g of 50 wt% ethanol aqueous solution, then added to the intermediate solution, pH 2, heated to 80°C for chelation reaction for 3 h; 10.30 g (0.062 mol) of triethyl phosphite was added, and small molecules were removed by vacuum distillation during the reaction to obtain a liquid titanium catalyst. The catalyst preparation conditions are shown in Table 1.

[0082] 830g of terephthalic acid, 387g of ethylene glycol, the titanium catalyst prepared above, and the matting agent slurry are added to the polymerization kettle for slurrying, wherein the titanium catalyst is added in an amount of 6ppm, based on the weight of Ti atoms relative to the polyester, and the matting agent is added in an amount of 0.3%, based on the weight of titanium dioxide relative to the polyester. After nitrogen replacement, the esterification reaction is carried out at 220-260°C and 0-0.4MPa, and the esterification water is discharged through separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the vacuum is evacuated and the decompression is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0083] Example 4 102.1 g (1.64 mol) of ethylene glycol, 34.03 g (0.1 mol) of tetrabutyl titanate and 4.1 g (0.05 mol) of sodium acetate were added to a three-necked flask equipped with a magnetic stirrer, a thermometer and a condenser, stirred and heated to dissolve, and the ester exchange reaction was carried out at 80 ° C for 2 h; 33.64 g (0.15 mol) of KL 4 Dibenzoylmethane was dissolved in 100.91 g of chloroethanol to prepare a solution, which was added to the ester exchange solution at a rate of 20 mL / min and refluxed for 3 h to obtain an intermediate. 3 Lactobionic acid was dissolved in 161.2 g of 50 wt% ethanol aqueous solution, then added to the intermediate solution, heated to 80°C for chelation reaction for 1 h, 25 wt% sodium hydroxide solution was added to adjust the pH to 3, and the chelation reaction was continued for 2 h; 110.30 g (0.062 mol) of triethyl phosphite was added, and small molecules were removed by vacuum distillation during the reaction to obtain a liquid titanium catalyst. The catalyst preparation conditions are shown in Table 1.

[0084] 830g of terephthalic acid, 387g of ethylene glycol, the titanium catalyst prepared above, and the matting agent slurry are added to the polymerization kettle for slurrying, wherein the titanium catalyst is added in an amount of 6ppm, based on the weight of Ti atoms relative to the polyester, and the matting agent is added in an amount of 0.3%, based on the weight of titanium dioxide relative to the polyester. After nitrogen replacement, the esterification reaction is carried out at 220-260°C and 0-0.4MPa, and the esterification water is discharged through separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the vacuum is evacuated and the decompression is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0085] Example 5 102.1 g (1.64 mol) of ethylene glycol, 34.03 g (0.1 mol) of tetrabutyl titanate and 4.1 g (0.05 mol) of sodium acetate were added to a three-necked flask equipped with a magnetic stirrer, a thermometer and a condenser, stirred and heated to dissolve, and the ester exchange reaction was carried out at 80 ° C for 2 h; 33.64 g (0.15 mol) of KL 4 Dibenzoylmethane was dissolved in 100.91 g of chloroethanol to prepare a solution, which was added to the ester exchange solution at a rate of 20 mL / min and refluxed for 3 h to obtain an intermediate. 3Lactobionic acid was dissolved in 161.2 g of 50 wt% ethanol aqueous solution and then added to the intermediate solution. The temperature was raised to 80° C. for chelation reaction for 1 h. A 25 wt% sodium hydroxide solution was added to adjust the pH to 3, and the chelation reaction was continued for 2 h. 13.86 g (0.062 mol) of triethyl phosphonoacetate was added, and small molecules were removed by reduced pressure distillation during the reaction to obtain a liquid titanium catalyst. The structural formula is shown below, and the catalyst preparation conditions are shown in Table 1.

[0086] 830g of terephthalic acid, 387g of ethylene glycol, the titanium catalyst prepared above, and the matting agent slurry are added to the polymerization kettle for slurrying, wherein the titanium catalyst is added in an amount of 6ppm, based on the weight of Ti atoms relative to the polyester, and the matting agent is added in an amount of 0.3%, based on the weight of titanium dioxide relative to the polyester. After nitrogen replacement, the esterification reaction is carried out at 220-260°C and 0-0.4MPa, and the esterification water is discharged through separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the vacuum is evacuated and the decompression is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0087] Example 6 102.1 g (1.64 mol) of ethylene glycol, 34.03 g (0.1 mol) of tetrabutyl titanate and 4.1 g (0.05 mol) of sodium acetate were added to a three-necked flask equipped with a magnetic stirrer, a thermometer and a condenser, stirred and heated to dissolve, and the ester exchange reaction was carried out at 80 ° C for 2 h; 33.64 g (0.15 mol) of KL 4 Dibenzoylmethane was dissolved in 100.91 g of chloroethanol to prepare a solution, which was added to the ester exchange solution at a rate of 20 mL / min and refluxed for 3 h to obtain an intermediate. 3 Lactobionic acid was dissolved in 161.2g of 50wt% ethanol aqueous solution, then added to the intermediate solution, heated to 80°C for chelation reaction for 1h, 25wt% sodium hydroxide solution was added to adjust the pH to 5, and the chelation reaction was continued for 2h; 13.86g (0.062mol) of triethyl phosphonoacetate was added, and small molecules were removed by reduced pressure distillation during the reaction to obtain a titanium catalyst. The catalyst preparation conditions are shown in Table 1.

[0088] 830g of terephthalic acid, 387g of ethylene glycol, the titanium catalyst prepared above, and the matting agent slurry are added to the polymerization kettle for slurrying, wherein the titanium catalyst is added in an amount of 6ppm, based on the weight of Ti atoms relative to the polyester, and the matting agent is added in an amount of 0.3%, based on the weight of titanium dioxide relative to the polyester. After nitrogen replacement, the esterification reaction is carried out at 220-260°C and 0-0.4MPa, and the esterification water is discharged through separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the vacuum is evacuated and the decompression is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0089] Example 7 102.1 g (1.64 mol) of ethylene glycol, 22.81 g (0.1 mol) of tetraethyl titanate and 4.1 g (0.05 mol) of sodium acetate were added to a three-necked flask equipped with a magnetic stirrer, a thermometer and a condenser, stirred and heated to dissolve, and the ester exchange reaction was carried out at 80 ° C for 2 h; 39.93 g (0.15 mol) of KL 3 2-Naphthoyltrifluoroacetone was dissolved in 119.8 g of chloroethanol to prepare a solution, which was added to the ester exchange solution at a rate of 20 mL / min and refluxed for 3 h to obtain an intermediate. 1 Mandelic acid was dissolved in 15.21 g of ethanol and then added to the intermediate solution. The temperature was raised to 80° C. for chelation reaction for 1 h. A 25 wt % sodium hydroxide solution was added to adjust the pH to 3, and the chelation reaction was continued for 2 h. 9.80 g (0.062 mol) of phenylphosphonic acid was added, and small molecules were removed by reduced pressure distillation during the reaction to obtain a liquid titanium catalyst. The catalyst preparation conditions are shown in Table 1.

[0090] 830g of terephthalic acid, 387g of ethylene glycol, the titanium catalyst prepared above, and the matting agent slurry are added to the polymerization kettle for slurrying, wherein the titanium catalyst is added in an amount of 6ppm, based on the weight of Ti atoms relative to the polyester, and the matting agent is added in an amount of 0.3%, based on the weight of titanium dioxide relative to the polyester. After nitrogen replacement, the esterification reaction is carried out at 220-260°C and 0-0.4MPa, and the esterification water is discharged through separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the vacuum is evacuated and the decompression is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0091] Example 8 102.1 g (1.64 mol) of ethylene glycol, 28.42 g (0.1 mol) of tetrapropyl titanate and 4.1 g (0.05 mol) of sodium acetate were added to a three-necked flask equipped with a magnetic stirrer, a thermometer and a condenser, stirred and heated to dissolve, and the ester exchange reaction was carried out at 80 ° C for 2 h; 57.33 g (0.15 mol) of KL 5 4,4'-Dibromodibenzoylmethane was dissolved in 172g of chloroethanol to prepare a solution, which was added to the ester exchange solution at a rate of 20mL / min and refluxed for 3h to obtain an intermediate. 4 N-acetylneuraminic acid was dissolved in 30.92 g of a 50 wt.% ethanol aqueous solution, and then added to the intermediate solution. The temperature was raised to 80° C. for chelation reaction for 1 h, and a 25 wt.% sodium hydroxide solution was added to adjust the pH to 3, and the chelation reaction was continued for 2 h. 6.07 g (0.062 mol) of phosphoric acid was added, and small molecules were removed by reduced pressure distillation during the reaction to obtain a liquid titanium catalyst. The catalyst preparation conditions are shown in Table 1.

[0092] 830g of terephthalic acid, 387g of ethylene glycol, the titanium catalyst prepared above, and the matting agent slurry are added to the polymerization kettle for slurrying, wherein the titanium catalyst is added in an amount of 6ppm, based on the weight of Ti atoms relative to the polyester, and the matting agent is added in an amount of 0.3%, based on the weight of titanium dioxide relative to the polyester. After nitrogen replacement, the esterification reaction is carried out at 220-260°C and 0-0.4MPa, and the esterification water is discharged through separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the vacuum is evacuated and the decompression is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0093] Example 9 102.1 g (1.64 mol) of ethylene glycol, 28.42 g (0.1 mol) of tetraisopropyl titanate and 4.1 g (0.05 mol) of sodium acetate were added to a three-necked flask equipped with a magnetic stirrer, a thermometer and a condenser, stirred and heated to dissolve, and the ester exchange reaction was carried out at 80 ° C for 2 h; 34.23 g (0.15 mol) of KL 7 Dissolve bipyridine-2-formylmethane in 102.7 g chloroethanol to prepare a solution, add it to the ester exchange solution at a rate of 20 mL / min, and reflux for 3 h to obtain an intermediate. 1Mandelic acid was dissolved in 15.21 g of ethanol and then added to the intermediate solution. The temperature was raised to 80° C. for chelation reaction for 1 h. A 25 wt % sodium hydroxide solution was added to adjust the pH to 3, and the chelation reaction was continued for 2 h. 19.2 g (0.062 mol) of triphenyl phosphite was added, and small molecules were removed by reduced pressure distillation during the reaction to obtain a liquid titanium catalyst. The catalyst preparation conditions are shown in Table 1.

[0094] 830g of terephthalic acid, 387g of ethylene glycol, the titanium catalyst prepared above, and the matting agent slurry are added to the polymerization kettle for slurrying, wherein the titanium catalyst is added in an amount of 6ppm, based on the weight of Ti atoms relative to the polyester, and the matting agent is added in an amount of 0.3%, based on the weight of titanium dioxide relative to the polyester. After nitrogen replacement, the esterification reaction is carried out at 220-260°C and 0-0.4MPa, and the esterification water is discharged through separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the vacuum is evacuated and the decompression is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0095] Example 10 The preparation process of the titanium catalyst is the same as that of Example 5.

[0096] 830g of terephthalic acid, 387g of ethylene glycol and matting agent slurry are added to the polymerization kettle for beating, wherein the amount of matting agent added is 0.3%, based on the weight of titanium dioxide relative to polyester. After nitrogen replacement, esterification reaction is carried out at 220-260℃ and 0-0.4MPa, and esterification water is discharged after separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the prepared titanium catalyst is added, and the amount of titanium catalyst added is 6ppm, based on the weight of Ti atoms relative to polyester, and stirred for 20min to mix evenly, vacuumed and reduced pressure, and the polycondensation temperature is controlled to be 278℃. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0097] Embodiment 11 The preparation process of the titanium catalyst is the same as that of Example 5.

[0098] 830g of terephthalic acid and 387g of ethylene glycol were added to the polymerization kettle for slurrying. After nitrogen replacement, the esterification reaction was carried out at 220-260℃ and 0-0.4MPa, and the esterification water was discharged after separation in the process tower and cooling in the condenser. After the esterification reaction was completed, the prepared titanium catalyst and matting agent slurry were added. The amount of titanium catalyst added was 6ppm, based on the weight of Ti atoms relative to the polyester, and the amount of matting agent added was 0.3%, based on the weight of titanium dioxide relative to the polyester. Stir for 20 minutes to mix evenly, evacuate and reduce pressure, control the polycondensation temperature to 278℃, and after low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt was cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0099] Example 12 The preparation process of the titanium catalyst is the same as that of Example 5.

[0100] 830g of terephthalic acid, 387g of ethylene glycol and matting agent slurry are added to the polymerization kettle for beating, wherein the amount of matting agent added is 2.2%, based on the weight of titanium dioxide relative to polyester. After nitrogen replacement, esterification reaction is carried out at 220-260°C and 0-0.4MPa, and esterification water is discharged after separation in the process tower and cooling in the condenser. After the esterification reaction is completed, the prepared titanium catalyst is added, and the amount of titanium catalyst added is 6ppm, based on the weight of Ti atoms relative to polyester, stirred for 20min to mix evenly, vacuumed and reduced pressure, and the polycondensation temperature is controlled to be 278°C. After low vacuum pre-polycondensation and high vacuum polycondensation reaction below 100Pa, after reaching the expected stirring power, the melt is cast, cooled underwater, and pelletized to obtain matte titanium polyester chips. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0101] Comparative Example 1 The titanium catalyst preparation method and polymerization evaluation method of this comparative example are basically the same as those of Example 5, except that the second ligand lactobionic acid is not added to the titanium catalyst. The catalyst preparation conditions are shown in Table 1, and the polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0102] Comparative Example 2 (conventional titanium catalyst) The polymerization evaluation method of this comparative example is basically the same as that of Example 5, except that tetrabutyl titanate is used as a catalyst. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0103] Comparative Example 3 (Conventional Titanium Catalyst) The polymerization evaluation method of this comparative example is basically the same as that of Example 5, except that titanium glycolate is used as the catalyst. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0104] Comparative Example 4 (Antimony Catalyst) The polymerization evaluation method of this comparative example is basically the same as that of Example 5, except that ethylene glycol antimony is used as the catalyst, and the amount of antimony catalyst added is 180 ppm, calculated as the weight of Sb atoms relative to the polyester. The polymerization evaluation conditions and polyester product indicators are shown in Table 2.

[0105] Performance Testing Table 1: Catalyst preparation conditions Table 2: Polymerization evaluation conditions and polyester product indicators The following conclusions can be drawn from Table 2: Examples 1-9 and Comparative Example 1 optimized the ligand composition, key preparation process, stabilizer, etc. of the titanium catalyst one by one. Among them, the titanium catalyst matting agent prepared in Example 5 has high tolerance, which greatly shortens the polycondensation reaction time and accelerates the polymerization rate. The titanium-based polyester has high thermal stability, and the product has better brightness and whiteness.

[0106] Examples 5, 10-11 use the same group of optimized titanium catalysts for polymerization, and compare the polycondensation catalytic performance of the titanium catalyst and the matting agent in different addition orders. The results show that there is no significant difference in the polycondensation time and the polyester product indicators. It can be concluded that the titanium catalyst prepared by the present invention has high tolerance to the matting agent, and its catalytic activity is not affected by the matting agent. Example 12 increases the amount of matting agent added to 2.2% on the basis of Example 10, and the polycondensation reaction rate is not affected, indicating that the titanium catalyst prepared by the present invention is suitable for the synthesis of fully matted titanium polyester.

[0107] Example 5 and Comparative Examples 2-4 compare the catalytic activity of different catalysts in synthesizing extinction polyester. Compared with conventional titanium catalysts, the titanium catalyst prepared by the present invention has significantly improved extinction agent tolerance, and its catalytic performance is equivalent to that of ethylene glycol antimony catalyst.

[0108] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0109] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A titanium-based polyester catalyst with high matting agent tolerance, characterized in that: It includes alkoxy titanium diol ester, and conjugated aromatic compounds chelated with the alkoxy titanium diol ester. β -Diketone and aromatic or alicyclic α -Hydroxy acids; Among them: conjugated aromatic β -diketone forms a six-membered ring chelate structure with the titanium active center of the alkoxytitanium diol ester through bidentate coordination; α The -hydroxy acid forms a five-membered ring chelate structure through the hydroxyl group, carboxylic acid and the titanium active center of the alkoxytitanium diol ester.

2. The titanium-based polyester catalyst with high matting agent tolerance according to claim 1, characterized in that: The alkoxytitanium is selected from at least one of tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetraisopropyl titanate, tetrabutyl titanate and tetraisooctyl titanate.

3. The titanium-based polyester catalyst with high matting agent tolerance according to claim 1, characterized in that: The conjugated aromatic β - diketone selected from benzoyl acetone, benzoyl trifluoroacetone, 2-naphthoyl trifluoroacetone, dibenzoyl methane, 4,4'-dibromodibenzoyl methane, dinaphthoyl methane and KL 7 At least one of bipyridine-2-formylmethane; and / or The conjugated aromatic β The molar ratio of diketone to alkoxytitanium is 0.2 to 4:

1.

4. The titanium-based polyester catalyst with high matting agent tolerance according to claim 1 or 3, characterized in that: The aromatic or alicyclic α - hydroxy acid is selected from at least one of mandelic acid, benzilic acid, lactobionic acid and N-acetylneuraminic acid; and / or The aromatic or alicyclic α The molar ratio of -hydroxy acid to alkoxytitanium is 0.2 to 4:

1.

5. The titanium-based polyester catalyst with high matting agent tolerance according to claim 1 or 2, characterized in that: It also includes a promoter selected from at least one of sodium acetate, potassium acetate, magnesium acetate, calcium acetate, zinc acetate, lanthanum acetate and cerium acetate; and / or The molar ratio of the co-catalyst to the alkoxy titanium is 0.2 to 2:

1.

6. The titanium-based polyester catalyst with high matting agent tolerance according to claim 5, characterized in that: Also includes a stabilizer, selected from at least one of orthophosphoric acid, phosphorous acid, hypophosphorous acid, phosphonic acid or their derivatives; The mass ratio of phosphorus atoms in the stabilizer to titanium atoms in the alkoxy titanium is 0.02 to 1:

1.

7. The titanium-based polyester catalyst with high matting agent tolerance according to claim 1 or 2, characterized in that: The diol is selected from at least one of ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, butylene glycol and pentanediol.

8. A method for preparing the titanium-based polyester catalyst with high matting agent tolerance according to any one of claims 1 to 5, characterized in that: include: 1) dispersing alkoxy titanium in diol for ester exchange reaction to obtain an ester exchange solution; Conjugated aromatic β -The alcohol solution of diketone is added to the ester exchange solution for chelation to obtain an intermediate solution; 2) Add aromatic or alicyclic α -Hydroxy acid is added to the intermediate solution for chelation; alkali is added to adjust the system to acidity and chelation is continued; The titanium-based polyester catalyst with high matting agent tolerance is obtained by distillation.

9. The preparation method according to claim 8, characterized in that: 1) In The conditions of the transesterification reaction are: temperature 60-120° C., time 1-3 h; and / or The chelating conditions are: chelating reaction at 60-120° C. for 2-6 hours.

10. The preparation method according to claim 8 or 9, characterized in that: 1) In The mass ratio of the diol to the alkoxytitanium is 0.5 to 10:1; and / or The conjugated aromatic β - the alcohol solvent of the alcohol solution of the diketone is selected from at least one of methanol, ethanol, isopropanol, chloroethanol and 1-chloro-2-propanol; and / or The alcohol solvent and the conjugated aromatic β - the mass ratio of diketone is 1 to 20:1; and / or The conjugated aromatic β The addition rate of the alcohol solution of -dione is 10-30 mL / min.

11. The preparation method according to claim 8, characterized in that: 2) In The chelating conditions are: temperature 80-150°C, time 1-2h; and / or The alkali is added to adjust the system to an acidic pH of 3 to 4; and / or The chelation duration is 2 to 4 hours.

12. The preparation method according to claim 8 or 11, characterized in that: 2) wherein the aromatic or alicyclic α -hydroxy acid is added in the form of a solution, the solvent is selected from at least one of water, methanol, ethanol, isopropanol and ether; the solvent is mixed with the aromatic or alicyclic α -The mass ratio of hydroxy acid is 0.5 to 10:

1.

13. The preparation method according to claim 8, characterized in that: 1), alkoxytitanium is dispersed in diol together with a co-catalyst.

14. The preparation method according to claim 8, characterized in that: 2) After continuing the chelation and before distillation, add the stabilizer.

15. Use of the high matting agent tolerant titanium-based polyester catalyst according to any one of claims 1 to 7 or the high matting agent tolerant titanium-based polyester catalyst obtained by the preparation method according to any one of claims 8 to 14 in the synthesis of matting polyester.

16. The use according to claim 15, characterized in that: The synthesis method of the matte polyester comprises: using dicarboxylic acid and / or its ester derivatives and diol as raw materials, carrying out esterification reaction to obtain an esterification product, and then carrying out pre-polycondensation and final polycondensation to obtain the matte polyester; In the above process, the titanium dioxide matting agent and the high matting agent tolerant titanium-based polyester catalyst are added at any stage before, during or after the esterification.

17. The use according to claim 16, characterized in that: The amount of the titanium dioxide matting agent added is 0.2-2.2wt% of the matting polyester; and / or Calculated in terms of titanium atoms, the addition amount of the high matting agent resistant titanium-based polyester catalyst is 4 to 20 ppm of the matting polyester.

18. The use according to claim 16 or 17, characterized in that: The dicarboxylic acid and / or its ester-forming derivative is at least one of terephthalic acid, phthalic acid, isophthalic acid, biphenyl dicarboxylic acid, 5-sodium sulfoisophthalate, dimethyl terephthalate, diethyl terephthalate, furandicarboxylic acid, oxalic acid, succinic acid and adipic acid; and / or The diol is at least one of ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, butylene glycol and pentanediol.

19. The use according to claim 16 or 17, characterized in that: The conditions of the esterification reaction are: temperature 220-260° C., pressure 0-0.4 MPa; The pre-polycondensation conditions are: 250-290°C, 10-15 kPa; The conditions for the final polycondensation are: 250-290° C., 50-150 Pa.

Citation Information

Cited By

  • High-performance TPEE elastomer and preparation method thereof

    CN121362317A

  • High performance tpee elastomer and method for its preparation

    CN121362317B